Biliary reflux after laparoscopic modified antireflux monoanastomotic gastric bypass surgery - M. V. Nikolaiev (Zaporozhye State Medical University, 2021)
Aim. Determination of biliary reflux in patients with morbid obesity after a single-anastomotic gastric bypass operation performed in the clinic's modification and according to the classical Roux-en-Y gastric bypass technique. Development of diagnostic criteria for biliary reflux Materials and methods. The results of treatment of 36 patients with morbid obesity who underwent bypass surgery were studied. The patients are divided into two groups. Clinically modified laparoscopic monoanastomotic gastric bypass surgery was performed in 25 patients (main group). The control group included 11 patients after the standard technique of Roux-en-Y laparoscopic gastric bypass. Inclusion criteria were: persons of both sexes aged 18-60 years with morbid obesity and a body mass index of 40 or more, as well as 35 or more in the presence of comorbid diseases (type 2 diabetes mellitus, arterial hypertension, dyslipidemia, sleep apnea syndrome). In both groups, impedance pH measurements were performed in the postoperative period. Statistical processing was performed using the Statistica 13.0 software package using parametric and nonparametric statistical methods. Results: Clinical manifestations of the enterogastric biliary reflex were found in both groups; in addition, clinical manifestations of the corresponding symptoms were noted by patients of both groups. The analysis of daily pH-metry in the studied groups showed that in the esophagus the time with pH <4 in the main group 2.83 (1.55; 3.95)% 3.00 (2.30; 3.50)% in the control group, time with pH 4-6.9 (physiological for the esophagus) 92.40 (90.65; 94.20)% and 94.10 (89.80; 95.50)%, respectively, time with pH> 7 (weak alkaline) was 4.80 (3.45; 5.85)% and in the control group 2.90 (1.20; 7.20)%. There was no statistically significant difference in these indicators (p> 0.05). Conclusions. Monoanastomotic gastric bypass surgery in the modification of the clinic has the same positive properties as the Rouen-Wye technique, allowing you to avoid the risks associated with possible pathological reflux of bile into the esophagus. Patients who have undergone mini-gastric bypass surgery require a thorough examination with fibrogastroscopy in combination with pH impedance measurement at least 1 time per year in order to determine biliary reflux and morphological changes both in the lumen of the esophagus and in the stomach stump. The level of quality of life of patients after surgery in the control group and the main group does not significantly differ, as evidenced by the results of the questionnaire survey using the GERG Q questionnaire, which indicates the effectiveness of the methodology of laparoscopic monoanastomotic gastric bypass surgery modified in the clinic.